Pengaruh perhatian guru, motivasi belajar, dan kecerdasan emosional terhadap prestasi belajar biologi siswa SMA Negeri 2 Bantul - Sudati Winarni (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
This research was aimed to know the effect of the teacher’s care and emotional cleverness in a group or partially to biology learning achievement of students at SMA N 2 Bantul. This research was correlation research. The subjects of the research were the students of class XII in exact sciences, SMA N 2 Bantul with the sample that consist of 127 students. To take the sample in this research used sampling random proportional technique. The sample sum was decided by using sample decision table from Issac and Michael by the result of 95 students. The technique of data collection used the questionnaire that was included the teacher’s care, learning motivation and emotional cleverness. The measurement of the biology learning achievement test that referring to passing competence standard. The instrument was tested to 32 students as the respondent. The instrument validity analysis that was questionnaire used the correlation of product moment and reliability with Cronbach Alpha. Before hypothesis test analysis, there was pretest such as normality test, linearity test, and multicollinearity test. To test hypothesis used double regression test and bivariate analysis. The effective and relative role of each variable were also counted. The result of this research shows (1)  that  there are positive that significant effect between teacher’s care, learning motivation and emotional cleverness to biology learning achievement, if teacher’s care, learning motivation, and emotional cleverness are hight so biology learning achievement is hight (2) partially the teacher’s care shows the positive that   significant effect to biology learning achievement, if teacher’s care hight so bilology learning achievement is hight.(3) the learning motivation shows the positive that significant effect to biology learning achievement, if learning motivation hight so biology learning achievement is hight (4) the emotional cleverness shows the positive that significant effect to biology learning achievement, if emotional cleverness hight so biology learning achievement is hight.